Pengembangan E-Modul Materi Kerajaan-Kerajaan Islam dalam Pembelajaran Sejarah Kelas X - Juliandry Kurniawan Junaidi; Tuti Khairani; Kaksim Kaksim (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2024)
This research is based on the lack of learning tools for students in the history learning process. At the time of learning, only some students get a learning book so that the teacher who explains the material is not optimal in explaining the material to the students. The purpose of this study is to find out the design, implementation, advantages and disadvantages of the development of e-modules of Islamic kingdoms material in class x history learning. The research method used in this study is research and development. The data analysis used in this study is 4-D. The results of the study are as follows, first, the validation test with a very valid category obtained an average score of 90.76% from various aspects of assessment. The aspect of media feasibility is 100% percent, the aspect of material feasibility is 87.5%, the aspect of language feasibility is 85% percent. Second, the teacher's practicality test with a score of 260 at the percentage level of 86.6% with the predicate "Very Practical". Third, the teacher feasibility test with an average score of 383 at the percentage level of 85.1% with the predicate "Very Feasible"